6 - Globalisation and Labour Utilisation in Nigeria: Evidence from the Construction Industry - Anugwom, Edlyne E. (Africa Development, 2007)
This study examines the influence of globalisation on labour utilisation in Ni- geria using the construction industry as a case study. It reveals that the era of globalisation has given rise to profound changes in the way labour is utilised, specifically in terms of employment patterns as well as the related issues of earnings, job security, unionisation etc. In effect, the way the worker is used by the firms in the industry is determined solely by the dictates of capitalism, i.e. the profit motive. The conclusion is that the consequences of globalisation have been unfavourable to the workers in the so-called ‘semi-skilled’ category. Thus, neo-liberal globalisation, contrary to the often-benevolent impacts attributed to it, has worsened rather than improved the situation of workers in the construc- tion industry in Nigeria. This then calls attention to the need for inter alia a more focused regulation of the activities of Multinational Corporations (MNCs) and the enforcement of minimum ILO standards in member countries, especially in the developing world where the need to attract the all important foreign invest- ment may override any other consideration.